Polusi Udara dan Permasalahan terhadap Kulit - Marcella Dena Fernanda; Hendra Tarigan Sibero; Hanna Mutiara (Medula, 2023)
Pollution has been shown to increasingly play a role in several common ailments, and the effects on the skin are no exception. Indoor and outdoor pollutants are widely distributed in urban and rural environments. WHO defines air pollution as contamination of the outdoor (ambient) and indoor (household) environment by any chemical, physical or biological agent that alters the natural characteristics of the atmosphere. Inhaled or ingested pollutants can be distributed throughout the body through the systemic circulation, making the exposed air a target for contaminants in the superficial and deep layers of the skin. The mechanisms by which pollutants may interact with human skin may differ based on each agent and its specific characteristics. Basic and clinical studies have provided growing evidence of the interaction of pollutants with the skin. Pollutants can activate skin metabolic and inflammatory pathways and induce oxidative stress by lowering antioxidant levels in particular. The skin is also a target for another known source of oxidative stress, namely UV radiation. The interaction of pollutants with UV light or the human skin microbiota requires further clinical investigation to evaluate their specific impact on skin health. Both outdoor and indoor pollution were found to increase signs of skin aging such as facial lentigines and wrinkles. Living in a polluted environment can also reduce skin moisture, increase the rate of sebum excretion and possibly worsen symptoms of chronic inflammatory skin diseases in both children and adults. Home location, type of work and diet all lead to internal and external exposure to a variety of pollutants, with clinical consequences that can accumulate or synergize. Pollutants are only one component of exposure which means that both internal and external factors must be considered when establishing pollution protection measures, which necessitates the development of standard methods for their evaluation. This literature review provides an overview of how pollutants affect the health of the skin.